Public-targeted interventions addressing antimicrobial resistance and antibiotic use in Sub-Saharan Africa: a scoping review - Mike Kesby; Winifred Maduko; Emmanuel Olamijuwon; Jo Mhairi Hale (BMJ Global Health)
Introduction Antimicrobial resistance (AMR) is a global health threat, with sub-Saharan Africa (SSA) experiencing the heaviest health burden and the highest AMR-related mortality. Most interventions in the region focus on hospital settings and provider behaviour, with few empirical papers discussing how theories inform those interventions specifically, community-centred interventions often lack a theoretical framework. However, using behavioural change theories can help us understand public behaviour around antibiotic usage and how to develop theoretically based interventions to maximise effectiveness. This scoping review critically investigates public-targeted interventions on AMR and antibiotic use within SSA, paying close attention to the theories underpinning those interventions. Given the concerning global rise in the spread of AMR and its severe implications, the situation may likely deteriorate if interventions are not significantly enhanced.Methods A comprehensive search of peer-reviewed literature published in three databases (PubMed, Web of Science and Google Scholar) between 1997 and 2023 was conducted to determine the extent, range and nature of existing studies in this area. This review used the Arksey and O’Malley five-step scoping review framework.Results The final review included seven publications, with three of the studies conducted in Ghana and the remaining studies carried out across other SSA nations. Findings revealed that AMR interventions were tailored to various demographics, including school children, parents, patients and online audiences. There is a notable lack of inclusive interventions for vulnerable populations, such as persons living with disabilities.Conclusion The study findings emphasise the critical need for more community-centred research and AMR interventions that integrate relevant theoretical frameworks while being appropriately tailored to local contexts.